Exploring the Relationship between Leadership Style and Local Culture to the Formation of Student Character and Personality at the Faculty of Social and Political Sciences - Dwi Prasetyo, Firmansyah; Marwiyah, Siti; Adelia Citra, Lovita; Ifana, Anila; Cahyani, Lintang Dwi Sagita; Wulandari, Dwi Ayu (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This study investigates the relationship between leadership styles employed by educators and the formation of character and personality among students at the Faculty of Social and Political Sciences. Utilizing qualitative methods, including direct observation and in-depth interviews, the research emphasizes how different leadership approaches can be adapted to align with local cultural contexts, facilitating better interaction between educators and students. It highlights that a strong personality is essential for future leaders, and thus, educators must employ effective leadership styles to positively influence their students. The findings indicate that the character and personality development of students is significantly shaped by the leadership styles of their educators. Furthermore, diverse leadership approaches can complement one another, contributing to a holistic development of students' character and personality in preparation for their future roles as leaders.